Pengaruh Waktu dan Suhu Penyimpanan Kompon Karet terhadap Karakteristik Vulkanisasi - Muh. Wahyu Syabani; Suharyanto Suharyanto; Mertza Fitra Agustian; Lestari Hetalesi Saputri (Universitas Jayabaya, 2023)
A rubber compound is an intermediate product resulting from mixing rubber with other additives before being molded through a vulcanization process. Frequently, there is a delay between the compounding process and vulcanization, therefore proper storage procedures must be prepared. The presence of a vulcanizing agent, activator, and accelerator in the compound allows the vulcanization reaction to occur during the storage period. This study aims to analyze the effect of the storage time and temperature of rubber compounds on rubber vulcanization characteristics. The rubber compound is stored at room temperatures of 25oC and 32oC. On the 1st, 3rd, and 5th day of storage, the compounds were tested using a rheometer to obtain vulcanization parameter data. The values of MH, ML, ts2, tc90, cure rate index (CRI), and effective torque of each treatment were studied. The results showed that the storage time of the compound affected each of the observed parameters. In the range of 5 days, the longer time indicates the formation of polysulfide crosslinks in the rubber polymer chain network. Higher storage temperature also faster reaction rate during storage. The increasing number of cross-links resulting a longer induction period dan vulcanization time, lower CRI, and effective torque.